Il futuro oggi - Storie per orientarsi tra studi e lavori by Ornella Scandella, Franco Angeli Editore, 2019 - Ferraro, Speranzina (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
Il futuro oggi - Storie per orientarsi tra studi e lavori deals with orientation and, in particular, with the complex moment and way in which each person faces choices during important moments of transition. Through the autobiographical account of the moment of choice by a number of privileged witnesses, the author aims to bring out both the factors that contributed to certain choices, and the characteristics and the way in which they were faced by each individual.